OF LOVE AND LOSS hardy yeats larkin. - McAlindon, T. (Thomas) ([S.l.] : ROUTLEDGE, 2022)
A study of the poetry of Hardy, Yeats, and Larkin in relation to their shared preoccupation with time, change, and loss, the most ancient and fertile theme in lyric and reflective verse, known to earlier English poets as mutability. Though the importance of the socio-political and ideological context is in every case acknowledged, the literary-history context is viewed as primary: hence the introductory survey of foundational Renaissance and Romantic poets with whose work Hardy, Yeats, and Larkin were thoroughly familiar. Although a preoccupation with the subject of time and change in the work of these three poets is a critical commonplace, no one has ever isolated it for special attention, or used it to link them either together or with their historical predecessors. This is an entirely new approach to their work. The critical methodology employed is evidential and analytical rather than theoretical, focussed throughout on the meaning and the mood of each poem and the distinctive individuality of each poet.
Keywords: Hardy, Thomas, -- 1840-1928 -- Criticism and interpretation; Yeats, W. B. -- 1865-1939 -- Criticism and interpretation; Larkin, Philip -- Criticism and interpretation; English poetry -- History and criticism; LITERARY CRITICISM / Poetry; LANGUAGE ARTS & DISCIPLINES / Rhetoric